STRATEGI KEPALA SEKOLAH DALAM PEMBINAAN PROFESIONALISME GURU - Andi Kaslin; Sitti Rumisa (Kelola: Journal of Islamic Education Management, 2021)
This study examines the principal’s strategy in fostering teachers’ professionalism at UPT SD Negeri 089 Masamba and finds supporting factors and inhibiting factors as well as solutions in overcoming the problem of techer professionalism development. This research as a descriptive research. The subject in this study were principal, teachers, and students while the object was the principal’s strategy in fostering teacher professionalism at UPT SD Negeri 089 Masamba. Data were collected through observation, interviews and documentation. The data is processed through data reduction, data presentation, and drawing conclusions. The result of the study shows that the leadership strategy of principal in conducting coaching greatly influenced the professionalism of teachers with the strategy implemented by the the principal. Teachers who teaches can be controlled properly so that with the implementation of strategies for teachers, they make teachers professional in the learninf process in the classroom. The obstacles faceb by the principal in carrying out the coaching is the managerial task of the principal making it difficult to carry out maximum guidance. The principal overcame the obstacles by agrreing on a coaching schedule both in groups and individually without being limited bt time so that it can be done whenever the teacher needs it and the principal also forms assistance consisting of senior teachers to assist the principal in coaching process.